2020
DOI: 10.17306/j.afs.0740
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum uric acid concentration and cardiovascular risk factors in normotensivepostmenopausal women with dyslipidemia

Abstract: Background. According to the latest recommendation for patients with hyperuricemia and high cardiovascular risk, the serum uric acid (SUA) concentration should be lower than 5 mg/dL (<298 μmol/L). Additionally, studies have shown that SUA concentration in participants with hyperuricemia correlates with some dietary factors. The aim of this study was to assess the relationship between SUA concentration and some cardiovascular risk factors. Material and methods. Fifty-six postmenopausal women with dyslipidemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In this study, female participants were postmenopausal, so because of the hormonal deficiency of estrogen that has shown uricosuric effects, women are more susceptible to hyperuricemia at this stage of life. 54 , 55 For the aforementioned reason, the direct relationships shown for some classes of polyphenols and uric acid in women might be because of reverse causality. Women's habits may have changed because of the diagnosis of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, female participants were postmenopausal, so because of the hormonal deficiency of estrogen that has shown uricosuric effects, women are more susceptible to hyperuricemia at this stage of life. 54 , 55 For the aforementioned reason, the direct relationships shown for some classes of polyphenols and uric acid in women might be because of reverse causality. Women's habits may have changed because of the diagnosis of hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…In potential acidogenesis of the diet, fruits and vegetables act as a hydrogen (H) buffer in comparison to, protein, potassium and magnesium which stimulate H production 17 . Previous studies that have investigated the association between dietary acid load and lipid profile or body composition reported controversial results 20‐25 . In contrast to Farhangi et al, Wu et al showed a positive relationship between DAL and CRP 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, female participants were postmenopausal, so due to the hormonal deficiency of oestrogen that has shown uricosuric effects, women are more susceptible to hyperuricemia at this stage of life (339,340). For the aforementioned reason, the direct relationships shown for some classes of polyphenols between uric acid in women might be due to reverse causality.…”
Section: Discussionmentioning
confidence: 99%